Allogeneic stem cells derived from human exfoliated deciduous teeth (SHED) for the management of periapical lesions in permanent teeth: Two case reports of a novel biologic alternative treatment - Madu Ghana Shyam Prasad; Juvva Ramakrishna; Duvvi Naveen Babu (Tabriz University of Medical Sciences, 2017)
Stem cells are the pluripotent cells that have the capacity to differentiate into other specialized cells. Recently, many experiments have been conducted to study the potentiality of stem cells in the tissue regeneration. We report two cases treated utilizing stem cells from human exfoliated deciduous teeth (SHED) in the management of periapical lesions in permanent teeth. Two normal human deciduous teeth from children, 7‒8 years of age, were collected to isolate stem cells. Two patients, one with periapical pathology alone and the other with periapical lesion along with an open apex in young permanent teeth, were selected for the study. After initial debridement of the root canals, homing of SHED was carried out and the access cavity was sealed using glass-ionomer cement. Clinical examination after 7 days, 30 days, 90 days, 180 days and 365 days revealed no symptoms. Closure of open apex and periapical tissue healing were observed radiographically at one-month review and maintained until 365-day review. Positive response to electric pulp testing was recorded for the treated teeth from the 3- to 12-month follow-ups. The treated cases demonstrated complete resolution of periapical radiolucency in a span of 30 days, which was faster than the conventional methods. SHED could be considred effective in treating the periapical lesions and open apex in permanent teeth.